Cardiac CT fractal analysis of LV noncompaction and common cardiomyopathies - Manohar, Ashish; Wong, Ashley; Castillo, Edgard; Gunderson, Allison; Mistelbauer, Gabriel; Bagherzadeh, Shadi Peighambari; Haddad, Francois; Caliskan, Kadir; Budde, Ricardo P.J.; Hirsch, Alexander; Lee, Seung-Pyo; Lee, Whal; et al. (Journal of cardiovascular computed tomography, 2025)
Left ventricular noncompaction (LVNC), or hypertrabeculation, is a myocardial condition that remains challenging to diagnose and differentiate from other cardiomyopathies. This study evaluated the ability of cardiac CT to differentiate between LVNC, hypertrophic cardiomyopathy (HCM), dilated cardiomyopathy (DCM), and controls using fractal analysis of LV trabeculae. Subjects with LVNC, HCM, DCM, as well as controls, who underwent coronary CT angiography were included. LV trabecular structure was quantified using fractal analysis on a stack of 15 short-axis CT images. For each subject, maximum (FDmax) and average (FDglobal) fractal dimensions were reported. A subset of subjects also had clinically acquired cardiac MRI (CMR) exams for comparison. One-way ANOVA, Pearson correlation, and Bland-Altman analysis were used for statistical analysis. The study included 313 subjects (median age: 58.8 [48.1–68.0] years, 153 male) categorized into Control (89), LVNC (46), HCM (106), and DCM (72) cohorts. FDmax was significantly higher in LVNC (1.379 ​± ​0.047) than in Control (1.305 ​± ​0.033), HCM (1.321 ​± ​0.040), and DCM (1.344 ​± ​0.054) cohorts; all p ​< ​0.001. Similarly, FDglobal was significantly higher in LVNC (1.279 ​± ​0.041) than in the other cohorts; all p ​< ​0.05. In a subset of 132 subjects with both CT and CMR exams, fractal dimensions from the two modalities were strongly correlated (r ​= ​0.63, p ​< ​0.0001), with CT-derived values being higher (1.337 ​± ​0.049 vs. 1.262 ​± ​0.045, p ​< ​0.0001). CT-derived fractal dimensions of LV trabecular structure were significantly higher in LVNC compared to control subjects, HCM, and DCM. CT-derived fractal dimensions strongly correlated with, but were higher than, those from cardiac MRI in the same subjects.